Dynamical analysis of dislocation‐associated factors in total hip replacements by hardware‐in‐the‐loop simulation. Issue 11 (17th April 2017) - Geier, Andreas; Kluess, Daniel; Grawe, Robert; Herrmann, Sven; D'Lima, Darryl; Woernle, Christoph; Bader, Rainer
ABSTRACT: Since dislocation of total hip replacements (THR) remains a clinical problem, its mechanisms are still in the focus of research. Previous studies ignored the impact of soft tissue structures and dynamic processes or relied on simplified joint contact mechanics, thus, hindered a thorough understanding. Therefore, the purpose of the present study was to use hardware‐in‐the‐loop (HiL) simulation to analyze systematically the impact of varying implant positions and designs as well as gluteal and posterior muscle function on THR instability under physiological‐like loading conditions during dynamic movements. A musculoskeletal multibody model emulated the in situ environment of the lower extremity during deep sit‐to‐stand with femoral adduction maneuver while a six‐axis robot moved and loaded a THR accordingly to feed physical measurements back to the multibody model. Commercial THRs with hard‐soft bearings were used in the simulation with three different head diameters (28, 36, 44 mm) and two offsets (M, XL). Cup inclination of 45°, cup anteversion of 20°, and stem anteversion of 10° revealed to be outstandingly robust against any instability‐related parameter variation. For the flexion motion, higher combined anteversion angles of cup and stem seemed generally favorable. Total hip instability was either deferred or even avoided even in the presence of higher cup inclination. Larger head diameters (>36 mm) and femoral head offsets (8 mm) deferred occurrence of prosthetic and bone impingement associated with increasing resisting torques. In summary, implant positioning had a much higher impact on total hip stability than gluteal insufficiency and impaired muscle function. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2557–2566, 2017.